Interacting possibilities between off-site manufacturing and building information modelling for performance improvement (Construction Economics and Building, 2025)
Building information modelling (BIM) and Off-site manufacturing (OSM) have been extensively studied as separate concepts, yet few studies have examined their combined application as a hybrid approach. The current immature level of BIM adoption and OSM's limited success in Australia urged this research to investigate the innovative simultaneous interactions of building information modelling (BIM) and off-site manufacturing (OSM) in the Australian construction industry, while its novel application in the larger global construction industry environment is equally considered crucial for the advancement of research in this sector. Structural equation modelling was applied to investigate complex relationships between dependent and independent variables. In this empirical study, 105 academic publications were reviewed to build a solid foundation to support the findings. The findings show that OSM and BIM are not widely used in Australia. Individually, these capabilities have had no considerable impact on the overall performance of projects. Also, BIM and OSM have constructively interacted when they are concurrently applied. The study concluded that systematic implementation of OSM–BIM interactions could improve key productivity indicators, followed by the performance improvement of projects. Implementing this OSM–BIM hybrid approach that aligns with the Diffusion of Innovation Theory is best applied at the planning and managerial stages to ensure a practical operating system in OSM-based projects supported by BIM.